Housing inequalities and health outcomes among migrant and refugee populations in high-income countries: a mixed-methods systematic review - Rana, Kritika; Kent, Jennifer L.; Page, Andrew (BMC public health, 2025)
Background Migrant and refugee populations are disproportionately affected by the housing crises reportedly impacting high-income countries around the globe. However, the health implications of housing inequalities within these communities and contexts remain relatively understudied. This review aimed to synthesise the evidence on housing and health inequalities prevalent among migrant and refugee populations in high-income countries, and to identify the pathways linking housing inequalities and health outcomes. Methods This systematic review employed the Joanna Briggs Institute (JBI) methodology for mixed-methods systematic reviews using a convergent integrated approach to synthesis and integration. Electronic database searches were conducted using Medline (OVID), Web of Science (ISI), Embase (OVID), PsycInfo (OVID), Scopus, and CINAHL (EBSCO), supplemented by grey literature searches on Google Scholar, MedNar, and WHOLIS. Eligible studies included quantitative, qualitative, and mixed methods designs focused on understanding how housing inequalities are associated with physical and mental health outcomes. Results A total of 65 studies published between 1995 and 2024 were included in this review, comprising 38 quantitative and 27 qualitative studies. Substandard housing conditions, such as overcrowding and poor ventilation, were consistently associated with adverse physical and mental health outcomes, including respiratory illnesses and experiences of anxiety and depression. The type of housing tenure also impacted both physical and mental health, specifically living in inadequate rental housing as opposed to self-owned homes, was linked with poorer physical health and increased risk of mental health issues. Similarly, housing insecurity stemming from unstable housing situations and insecure tenancy, as well as neighbourhood conditions such as safety concerns and living in deprived neighbourhoods, led to the exacerbation of both physical and mental health issues. Furthermore, housing affordability challenges and decreased housing satisfaction were linked with poor mental health outcomes such as experiences of depression and psychological distress. Conclusions This review highlights the critical role of housing as a social determinant of health and wellbeing for migrant and refugee populations in high-income countries, along with highlighting the potential pathways through which housing inequalities impact physical and mental health outcomes. Ensuring access to adequate, affordable, and secure housing, while also improving neighbourhood conditions, is essential for improving the health and wellbeing of migrant and refugee populations.